Simulations of irradiated-enhanced segregation and phase separation in Fe–Cu–Mn alloys. (13th June 2017) - Li, Boyan; Hu, Shenyang; Li, Chengliang; Li, Qiulin; Chen, Jun; Shu, Guogang; Henager, Chuck; Weng, Yuqing; Xu, Ben; Liu, Wei
Abstract: For reactor pressure vessel steels, the addition of Cu, Mn, and Ni has a positive effect on their mechanical, corrosion and radiation resistance properties. However, experiments show that radiation-enhanced segregation and/or phase separation is one of the important material property degradation processes. In this work, we develop a model integrating rate theory and phase-field approaches to investigate the effect of irradiation on solute segregation and phase separation. The rate theory is used to describe the accumulation and clustering of radiation defects, while the phase-field approach describes the effect of radiation defects on phase stability and microstructure evolution. The Fe–Cu–Mn ternary alloy is taken as a model system. The free energies used in the phase-field model are from CALPHAD. Spatial dependent radiation damage from atomistic simulations is introduced into the simulation cell for a given radiation dose rate. The radiation effect on segregation and phase separation is taken into account through the defect concentration dependence of solute mobility. Using the model, the effect of temperature and radiation rates on Cu and Mn segregation and Cu-rich phase nucleation were systematically investigated. The segregation and nucleation mechanisms were analyzed. The simulations demonstrate that the nucleus of Cu precipitates has a core–shell composition profile, i.e. Cu-rich at the center and Mn-rich at the interface, in good agreement with theoretical calculations as well as experimental observations.